Genome Size Variation of Chagas Disease Vectors of the Rhodniini Tribe - Merle, Marie; Filée, Jonathan; de Oliveira, Jader [UNESP]; Almeida, Carlos Eduardo; Mougel, Florence; Bastide, Héloïse; Girondot, Marc; da Rosa, João Aristeu [UNESP]; Harry, Myriam (American Society of Tropical Medicine and Hygiene, 2022)
The genome size of five Rhodnius species (R. milesi, R. nasutus, R. neivai, R. prolixus, and R. robustus) and two Psammolestes species (P. coroedes and P. tertius) were estimated using flow cytometry and/or k-mer distributions in genome sequences. Phylogenetic generalized linear mixed models highlighted significant genome size variations among species and between sexes, with R. prolixus showing the largest genome. In this study we provide the first data on female genome size in Triatominae. For five species, female genome size did not differ from males, except for R. robustus, where females had smaller genomes. Genome size estimations based on the k-mer distribution method were less than those estimated from flow cytometry, but both methods exhibited the same pattern of sexual differences. Further genomic studies are needed to infer whether genome size variation could be an adaptive trait in Rhodnius.